Evaluation of Bio-rational Insecticides and Bio-pesticides Against Pod Borer Complex in Pigeon Pea - Das, Bilash Chandra; Patra, Sandip; Samanta, A.; Dhar, P. P. (International Journal of Bio-resource and Stress Management, 2022)
The field experiments were conducted at Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal, India during kharif seasons (July–October) of 2013 and 2014 to evaluate the efficacy of different bio-rational pesticides against the major production constrains of the pigeon pea which is the pod borer complex. The experiments were laid out following randomized block design comprising eleven treatments including control with three replications. Treatments were applied twice with pneumatic knapsack at fifteen days interval starting with initiation of target pest at pod formation stage. Pre-treatment counts of larvae of different lepidopteran borers had been taken from arbitrarily selected five tagged plants from every replication discarding the border effect and subsequently post treatment counts have been taken at 3, 7 and 14 days after each spray. Number of maggots per pod had been recorded for pod fly infestation at before spray and after spray at 7 and 14 days after each spray. Pooled of two years results revealed that flubendiamide recorded lowest mean larval population of Helicoverpa armigera (0.98 larvae plant-1) and Maruca vitrata (0.65 larvae plant-1) with highest seed yield.Among the bio-pesticides, Bacillus thuringiensis and azadirachtinfound to beeffective against pod borer complex in pigeon pea. Pooled of two seasons data showed that fenvalerate, spinosad and flubendiamide were effective treatments against pod fly with 1.13, 1.63 and 1.75 maggots pod-1 respectively.